Evaluation Of Vaccine Wastage in Surat - Mehta, Shreyash; Umrigar, Pradeep; Patel, Prakash; Bansal, R K (National Journal of Community Medicine, 2013)
Introduction: Vaccine wastage is one of the key factors to be considered with regards to vaccine forecasting and need estimation. Objective: This study was conducted to assess the amount of vaccine wastage; its correlation with type of vaccine and place of vaccination; with route of administration and wastage and with beneficiaries per session and wastage factor (WF). Methods and Materials: Session wise data on vaccine usage and its beneficiaries were collected from 36 Urban health centre (UHC) of Surat Municipal Corporation (SMC). Vaccine wastage rate ,vaccine wastage factor were calculated for each type of vaccine and each site of session and correlation analysis was done between the variables beneficiaries per session and wastage factor per session. Results: The overall wastage factor for BCG vaccine was 1.83, for OPV was 1.33, for DPT was 1.19, for Hepatitis B vaccine was 1.26 and for Measles vaccine was 1.39. The WF was highest for sessions held at ICDS for BCG vaccination (3.38) followed by sessions held at mobile sites for BCG vaccination (2.50). The WF was lowest for sessions held at UHC for DPT vaccination (1.11) followed by sessions held at subcentres for DPT vaccination (1.13) and sessions held at UHC for Hepatitis vaccination (1.13). Conclusions: BCG vaccine and Measles vaccine had WF greater than the allowable WF 1.33, OPV had WF of 1.33, DPT vaccine and Hepatitis vaccine had WF less than 1.33. WF was less for fixed sites of vaccination like the UHCs and subcentres while the WF was more ICDS and mobile sites.